2015
DOI: 10.3390/catal5031152
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Catalytic Hydrodeoxygenation of Guaiacol over Pt/SiO2 and Pt/H-MFI-90

Abstract: Hydrodeoxygenation of guaiacol in the presence of 1-octanol was studied in a fixed-bed reactor under mild conditions (50-250 °C) over platinum particles supported on silica (Pt/SiO2) and a zeolite with framework type MFI at a Si/Al-ratio of 45 (Pt/H-MFI-90). The deoxygenation selectivity strongly depended on the support and the temperature. Both guaiacol and octanol were rapidly deoxygenated in the presence of hydrogen over Pt/H-MFI-90 at 250 °C to cyclohexane and octane, respectively. In contrast, Pt/SiO2 mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…Used Pt/H-MFI-90 catalysts with coke deposition were washed with ethanol and methanol, calcined in air at 400 • C for 10 h and reduced in a continuous hydrogen flow [103]. The regeneration experiments for HDO of guaiacol and 1-octanol showed that the catalytic conversion of guaiacol and 1-octanol over recovered Pt/H-MFI-90 catalysts was partly restored, and the recovered catalyst deactivated faster than the fresh catalyst.…”
Section: Catalyst Regeneration and Recycle In Bio-oil Hdomentioning
confidence: 99%
“…Used Pt/H-MFI-90 catalysts with coke deposition were washed with ethanol and methanol, calcined in air at 400 • C for 10 h and reduced in a continuous hydrogen flow [103]. The regeneration experiments for HDO of guaiacol and 1-octanol showed that the catalytic conversion of guaiacol and 1-octanol over recovered Pt/H-MFI-90 catalysts was partly restored, and the recovered catalyst deactivated faster than the fresh catalyst.…”
Section: Catalyst Regeneration and Recycle In Bio-oil Hdomentioning
confidence: 99%
“…Size distribution could not be determined due to the occlusion of Rh particles within the zeolite channels, resulting in a difficulty to distinguish the particles from the support with this technique. These results indicate that small and well‐dispersed Rh nanoparticles can be synthesized on the surface of zeolite …”
Section: Resultsmentioning
confidence: 98%
“…Unfortunately, the conversion of guaiacol under typical FCC conditions resulted in coke deposition, responsible for pore obstruction and zeolite catalytic site poisoning . The development of durable, regenerable, and highly active bifunctional catalysts, such as the ones described in this manuscript, would mitigate the deactivation pathways, avoiding the formation of condensates and extending the catalyst operation life without affecting the octane rating …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, high temperatures require more energy consumption and thus an increase in cost. Recently, much attention has been focused on the liquid phase hydrogenation of phenols [8,[17][18][19][20][21][22][23][24][25]. For example, Huang et al [26] prepared a high-performance PdRu bimetallic catalyst on mesoporous silica nanoparticles for the hydrogenation of phenol in CH 2 Cl 2 solvent.…”
Section: Introductionmentioning
confidence: 99%